A laddering study of motivational complexities in mobile shopping. Issue 2 (7th March 2019) - Park, Ha Eun; Yap, Sheau Fen Crystal; Makkar, Marian
Abstract : Purpose: The purpose of this paper is to uncover the motivational tensions underlying mobile shopping (m-shopping) behaviours. The authors focus on consumer motivations and the pursuit of life end goals with respect to m-shopping. Design/methodology/approach: Based on the means-end chain theory, hard-laddering approach was used to elicit associations between attributes, consequences and values from 251 online participants. Content analysis was used to develop a hierarchical value map "mapping" these associations to uncover underlying values for m-shopping. Findings: Mobile shoppers are motivated by their self-actualisation needs (self-focused) and/or social needs (other-focused). Participants' response contradictions reflected internal complexities and ambivalences during their purchasing decisions. Decisions are based on their concerns around security, time, technological or financial. Practical implications: This study provides managerial insights into retail marketing and strategies. Marketers should consider creating user-friendly applications by researching the customer journey experience, heightening security measures and ensuring that added-value offers are clearly communicated to meet consumers' personal values and motivations. Originality/value: The paper presents an original conceptual contribution of personal values related to m-shopping as desires for self-empowerment, altruism and relationships with others, self-fulfilment and hedonism and possible consumer internal conflicts.